2014
DOI: 10.1242/jcs.155101
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90α forms a stable complex at cilia neck for signal molecules interaction in cilia-mediated IGF-1 receptor signaling

Abstract: The primary cilium is composed of an axoneme that protrudes from the cell surface, a basal body beneath the membrane and a transition neck in between. It is a sensory organelle on the plasma membrane, involved in mediating extracellular signals. In the transition neck region of the cilium, the microtubules change from triplet to doublet microtubules. This region also contains the transition fibres that crosslink the axoneme with the membrane and the necklace proteins that regulate molecules being transported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
(62 reference statements)
2
18
0
Order By: Relevance
“…In contrast, mouse club cells transdifferentiate into goblet cells in vivo (15,(135)(136)(137)(138). Interestingly, heat shock-induced dissociation of HSP90 from cilia leads to cilia resorption (95). Previous reports suggest but do not demonstrate that goblet cells might transdifferentiate into ciliated or other cell types (10,139).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, mouse club cells transdifferentiate into goblet cells in vivo (15,(135)(136)(137)(138). Interestingly, heat shock-induced dissociation of HSP90 from cilia leads to cilia resorption (95). Previous reports suggest but do not demonstrate that goblet cells might transdifferentiate into ciliated or other cell types (10,139).…”
Section: Discussionmentioning
confidence: 94%
“…In Tetrahymena and Chlamydomonas , flagellar defects due to partial loss of IFT proteins can be bypassed in some suppressor strains under conditions of oxygen deprivation [80, 9193], and it has been suggested that a stress-induced chaperone mechanism stabilizes the IFT-B complex to permit cilia function under these conditions [92]. Moreover, Hsp90 is localized to cilia, and regulates cilia stability in response to stress in mammalian cells [9496]. Our observations indicate that while IFT protein function is essential for ciliogenesis, compromised IFT complex function can be partly bypassed during early stages of adult aging or under other conditions of stress to promote cilia lengthening.…”
Section: Discussionmentioning
confidence: 99%
“…In Tetrahymena and Chlamydomonas, flagellar defects due to partial loss of IFT proteins can be bypassed in some suppressor strains under conditions of oxygen deprivation [80,[91][92][93], and it has been suggested that a stress-induced chaperone mechanism stabilizes the IFT-B complex to permit cilia function under these conditions [92]. Moreover, Hsp90 is localized to cilia, and regulates cilia stability in response to stress in mammalian cells [94][95][96]. Our observations indicate that while IFT protein function is essential for ciliogenesis, compromised IFT complex function can be partly bypassed during early stages of adult aging or under other conditions of stress to promote cilia lengthening.…”
Section: Discussionmentioning
confidence: 99%